Characterization of the Castanopsis carlesii Deadwood Mycobiome by Pacbio Sequencing of the Full-Length Fungal Nuclear Ribosomal Internal Transcribed Spacer (ITS) - Purahong, Witoon; Mapook, Ausana; Wu, Yu-Ting; Chen, Chaur-Tzuhn (Frontiers in Microbiology, 2019)
Short-read Next Generation Sequencing (NGS) platforms can easily and quickly generate thousands to hundreds of thousands of sequences per sample. However, the limited length of these sequences can cause problems during fungal taxonomic identification. Here we validate the use of Pacbio sequencing, a long-read NGS method, for characterizing the fungal community (mycobiome) of Castanopsis carlesii deadwood. We report the successful use of Pacbio sequencing to generate long-read sequences of the full-length (500 – 780 bp) fungal ITS regions of the Castanopsis carlesii mycobiome. Our results show that the studied deadwood mycobiome is taxonomically and functionally diverse, with an average of 85 fungal OTUs representing five functional groups (animal endosymbionts, endophytes, mycoparasites, plant pathogens, and saprotrophs). Based on relative abundance data, Basidiomycota were the most frequently detected phyla (50% of total sequences), followed by unidentified phyla and Ascomycota. However, based on presence/absence data, the most OTU-rich phyla were Ascomycota (58% of total OTUs, 72 OTUs) followed by Basidiomycota and unidentified phyla. The majority of fungal OTUs were identified as saprotrophs (70% of successfully function-assigned OTUs) followed by plant pathogens. Finally, we used phylogenetic analysis based on the full-length ITS sequences to confirm the species identification of 14/36 OTUs with high bootstrap support (99 – 100%). Based on the numbers of sequence reads obtained per sample, which ranged from 3,047 to 13,463, we conclude that Pacbio sequencing can be a powerful tool for characterizing moderate- and possibly high-complexity fungal communities.